Third Phase of Test Development and Testing Practice in the Republic of Croatia - 1952-1992 - Matešić, Krunoslav (Array, 2006)
Numerous papars on the history of psychology have been published in Croatia - covering the general development of psychology, the life and work of eminent psychologists, establishment of departments etc. However, test development and testing practices have not been completely covered in the literature. The autor has published several works in this field and considers that test development and testing practices, as important indicators of applied psychology development in Croatia, can be divided into four stages. The first was a sporadic period, i.e., tests were randomly published, beginning in 1912 with the first translation of the Binet-Simon scale and ending in 1931 with the establishment of the Councelling centre for career choice in Zagreb. The Councelling centre opens on 2nd January 1932, marking the second stage, which lasts until 1948 when political circumstances resulted in the abolishment of tests. The third stage begins with the reestablishment of professional guidance in 1952 and ends, after several subphases, with Croatian independence in 1992. The fourth period began with independence. With a short comment on the first two stages, the autor systematically covers the third period of tests and testing practices in the Republic of Croatia, lasting 1952 and 1992.